Implementasi Pendidikan Karakter Jepang Dalam Perspektif Islam Di Madrasah Aliyah Negeri 2 Kota Kediri - Exa Maya, Fismarada Agvi (An Naba, 2023)
This research contains the process of implementing Japanese character education at MAN 2 Kediri City. The type of research used in this research is qualitative research. The information collection technique in this research is through observation, interviews and documentation. The results of this research prove that some MAN 2 Kediri City students have not implemented their character education in their daily life at school. Some other students have implemented their character education, such as coming to school on time, regularly attending group prayers, having a respectful and polite attitude towards teachers or older people. The characters possessed by each student are an attitude of never giving up, being able to work well with friends, and having a high enthusiasm for learning which can be proven when the students will take part in high school/MA and national level competitions. The students are always enthusiastic about practicing from the time the school bell rings until the school bell rings. Globally, it can be said that MAN 2 Kediri City students have superior personalities so they are able to become the nation's next generation of quality.